THE INFLUENCE OF IDEOLOGICAL PROCESSES ON THE NATIONAL IDEA IN THE CONTEXT OF GLOBALIZATION - Karimov Ozodbek; Gulomova Diyora (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article separately highlights the moral threats directed at Uzbekistan in the process of globalization and the influence of ideological processes on the national idea, the issues of preserving the consciousness of the young generation from various harmful ideas and ideologies.